Facing emotions in narcolepsy with cataplexy: haemodynamic and behavioural responses during emotional stimulation. (21st February 2014) - de Zambotti, Massimiliano; Pizza, Fabio; Covassin, Naima; Vandi, Stefano; Cellini, Nicola; Stegagno, Luciano; Plazzi, Giuseppe
Summary Narcolepsy with cataplexy is a complex sleep disorder that affects the modulation of emotions: cataplexy, the key symptom of narcolepsy, is indeed strongly linked with emotions that usually trigger the episodes. Our study aimed to investigate haemodynamic and behavioural responses during emotional stimulation in narco‐cataplexy. Twelve adult drug‐naive narcoleptic patients (five males; age: 33.3 ± 9.4 years) and 12 healthy controls (five males; age: 30.9 ± 9.5 years) were exposed to emotional stimuli (pleasant, unpleasant and neutral pictures). Heart rate, arterial blood pressure and mean cerebral blood flow velocity of the middle cerebral arteries were continuously recorded using photoplethysmography and Doppler ultrasound. Ratings of valence and arousal and coping strategies were scored by the Self‐Assessment Manikin and by questionnaires, respectively. Narcoleptic patients' haemodynamic responses to pictures overlapped with the data obtained from controls: decrease of heart rate and increase of mean cerebral blood flow velocity regardless of pictures' content, increase of systolic blood pressure during the pleasant condition, and relative reduction of heart rate during pleasant and unpleasant conditions. However, when compared with controls, narcoleptic patients reported lower arousal scores during the pleasant and neutral stimulation, and lower valence scores during the pleasant condition, respectively, and also a lower score at the 'focus on and venting of emotions' dimensions of coping. Our results suggested that adult narcoleptic patients, compared with healthy controls, inhibited their emotion‐expressive behaviour to emotional stimulation, and that may be related to the development of adaptive cognitive strategies to face emotions avoiding cataplexy.